2017
DOI: 10.1088/1755-1315/60/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Removal of nickel ion from electroplating wastewater using double chamber electrodeposition cell (DCEC) reactor partitioned with water hyacinth (Eichhornia crassipes) leaves

Abstract: PAPER • OPEN ACCESSRemoval of nickel ion from electroplating wastewater using double chamber electrodeposition cell (DCEC) reactor partitioned with water hyacinth (Eichhornia crassipes) leaves Abstract. Nickel is a heavy metal present in many types of industrial wastewater, and its contamination to the water bodies should be prevented. The objective of this research was to study the performance of Double Chamber Electrodeposition Cell (DCEC) for nickel ion removal. Water hyacinth (Eichhornia crassipes) leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Many studies on the kinetics of nickel electrodeposition from an aqueous solution have been published [13]- [24].Most of these studies studied the kinetics based on charge-transfer controlled electrode kinetics [13], [14] or diffusionkinetic control associated with a typical nucleation process [15], [24 ]. A few studies were performed to study the kinetics of nickel removal under mass transfer contro [16], [17]. Djaenudin et al (2017) investigated the kinetics of nickel removal using a double chamber electrodeposition cell (DCEC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on the kinetics of nickel electrodeposition from an aqueous solution have been published [13]- [24].Most of these studies studied the kinetics based on charge-transfer controlled electrode kinetics [13], [14] or diffusionkinetic control associated with a typical nucleation process [15], [24 ]. A few studies were performed to study the kinetics of nickel removal under mass transfer contro [16], [17]. Djaenudin et al (2017) investigated the kinetics of nickel removal using a double chamber electrodeposition cell (DCEC).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies were performed to study the kinetics of nickel removal under mass transfer contro [16], [17]. Djaenudin et al (2017) investigated the kinetics of nickel removal using a double chamber electrodeposition cell (DCEC). They found that nickel ion removal in DCEC followed a first-order kinetic with a removal rate constant k = 0.12 h-1 (R2= 0.956).…”
Section: Introductionmentioning
confidence: 99%
“…Such biological materials can be microbial biomass, agricultural waste, industrial by-product or natural material, which has been heralded as a promising biotechnology for metal removal due to their high efficiency, low cost and large abundance (Gadd, 2009;Kurniawan et al, 2006a). For example, water hyacinth has been used as cell separator to reduce Ni concentration from 2200 g/L to 0.4 g/L in 72 h (Djaenudin et al, 2017). Different mechanism could be included in biosorption, such as absorption, ion exchange, complexation and precipitation (Figure 1-8).…”
Section: Biosorptionmentioning
confidence: 99%